2014
DOI: 10.1016/j.combustflame.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A high-pressure rapid compression machine study of n-propylbenzene ignition

Abstract: This study presents new ignition delay data recorded in a rapid compression machine over a wide range temperature, pressure and fuel/air ratio. This data is an extension of that recorded previously (D. Darcy, C.J. Tobin, K. Yasunaga, J.M. Simmie, J. Würmel, T. Niass, O. Mathieu, S.S. Ahmed, C.K. Westbrook, H.J. Curran, Combust. Flame, 159 (2012) 2219-2232 for the oxidation of n-propylbenzene in a high-pressure shock tube. The data was obtained for equivalence ratios of 0.29, 0.48, 0.96, and 1.92, at compresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 38 publications
0
60
0
1
Order By: Relevance
“…It has a twin opposed piston configuration. The heating system has been described by Darcy et al [43]. Pressure profiles are recorded using a pressure transducer (Kistler 603B) with the signal passing through a charge amplifier and recorded on a digital oscilloscope.…”
Section: Rapid Compression Machinementioning
confidence: 99%
“…It has a twin opposed piston configuration. The heating system has been described by Darcy et al [43]. Pressure profiles are recorded using a pressure transducer (Kistler 603B) with the signal passing through a charge amplifier and recorded on a digital oscilloscope.…”
Section: Rapid Compression Machinementioning
confidence: 99%
“…The sub-mechanism for these polycyclic aromatic species has been derived from the Narayanaswamy et al mechanism [12]. A more detailed discussion on the changes introduced in the toluene submechanism can be found in [44].…”
mentioning
confidence: 99%
“…As described in our recent n-propylbenzene paper [44], the addition reactions of the benzyl radical to molecular oxygen, an important step in the low temperature mechanisms of alkylbenzenes in general, have been derived by fitting over the temperature range of interest (600-900 K) the reaction rates that have been theoretically calculated by Murakami et al [46] for the xylyl + O 2 system. The reaction rate for the concerted elimination of HȮ 2 radical from the alkylperoxy species have been derived from Altarawneh et al [47], as in [44].…”
mentioning
confidence: 99%
“…Thus, congeners of alkyl aromatics may serve as surrogates replicating intrinsic chemical and physical properties of real fuels [1,2]. In particular, n-propylbenzene (nPB) embodies well the properties of a class of alkyl benzenes in jet and diesel fuels [3,4]. Previous studies have targeted several combustion characteristics of nPB, including ignition delay [5], laminar burning velocity [6] and sooting tendency [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of scarcity of kinetic measurements pertinent to reactions of nPB with C x H y and O/H radicals, the studies adopted the reaction rate constants from analogous oxidation systems such as propane, ethylbenzene and toluene. In reference to thermal decomposition and pyrolysis of nPB, Robinson and Lindstedt reported theoretically-derived rate constants for abstraction of an H atom from the propyl side chain in nPB, by H and CH 3 radicals [14]. Darcy et al [4] predicted the oxidation mechanism of nPB at low temperature to be greatly influenced by the reaction sequence: RH + HO 2 → R + H 2 O 2 , H 2 O 2 + M → 2OH + M. The authors have shown that at 1000 K, HO 2 and benzyl radicals govern the overall oxidation reactivity of nPB.…”
Section: Introductionmentioning
confidence: 99%